PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII3 SMP NEGERI 17 PEKANBARU - Rahmawati Rahmawati; Rini Dian Anggraini; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning cooperative technique Think Pair Share (TPS) model. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection.The research subject of this research is student of class VIII3 SMPN 17 Pekanbaru in academic years 2018/2019, which amounted to 39 students, consist of 23 boys and 16 girls. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative descriptive, while the students’ Mathematic tests were in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test I and II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (43,59%)to the first test (56,41%) to the second test II (61,53%). For the skills of basic score (38,46%) to the first test (43,59%) to the second test (64,10%), Results of this research indicates that appication of the learning cooperative technique Think Pair Share (TPS) model can improve learning process and increase mathematics achievement from the students at class VIII3 SMPN 17 Pekanbaru the second academic years 2018/2019 for the subject matter Circle.Key Words : Mathematics Achievement, Learning Cooprative Technique Think Pair Share (TPS)